The relationship between REITS and stock market prices during periods of volatility: a Bivariate GARCH analysis - Makara, Ntsali Audrey (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The relationship between real estate and the stock market is essential because they are the two most highly invested assets. In addition, examining the volatility of any asset is important for risk management and investor portfolio returns. The general motivation for analysing the relationship is that it can provide insight to policymakers and investors about the behaviour of stocks and real estate assets. The purpose of this research is to examine the relationship between Real Estate Investment Trusts (REITS) and stock prices in South Africa using daily data from 2 January 2013 to 31 May 2023. The wealth and credit effects are the two mechanisms used to interpret the relationship. The wealth effect is a mechanism that states that the causal relationship between the two markets runs from increasing stock prices which tends to increase real estate. The credit effect claims that real estate prices influence stock prices. Most of the existing literature has examined the relationship between the two markets but less attention has been given to the volatility spillover effects. Therefore, the analysis presented in this thesis extends the existing research by examining the relationship and the spillover effects between the REITs and stock markets. The study employs quantitative research methodology using the following econometric methods i)Vector Autoregression model, ii) Granger Causality Tests and Bivariate GARCH models. The study found that there is no long-run relationship between REITS and stock prices. In addition, the Granger Causality results showed a unidirectional relationship between REITs and stock prices. The results indicate the presence of a wealth effect in South Africa, meaning that changes in stock prices influence the real estate market. Moreover, the GARCH analysis found volatility spillover effects from the stock to the REITs markets. These results are helpful for policymakers and investors interested in the portfolio and risk management of the two markets.
Keywords: Real estate investment trusts -- South Africa; Stocks Prices; Stock exchanges -- South Africa; GARCH model; Volatility